In-field evaluation of clinoptilolite feeding efficacy on the reduction of milk aflatoxin M1 concentration in dairy cattle. Issue 1 (December 2016) - Katsoulos, Panagiotis; Karatzia, Maria; Boscos, Constantinos; Wolf, Petra; Karatzias, Harilaos
Abstract Background Clinoptilolite is a natural zeolite with high adsorption capacity for polar mycotoxins such as aflatoxins. The efficacy of clinoptilolite in ameliorating the toxic effects of aflatoxicosis has been proven in monogastric animals, but there is no such evidence for ruminants. The aim of this study was to evaluate, under field conditions, whether the dietary administration of clinoptilolite in dairy cows could reduce the concentration of aflatoxin M1 (AFM1 ) in bulk-tank milk, in farms with higher than or close to 0.05 μg/kg of milk (European maximum allowed residual level). An objective of the present study was also to investigate the effect of particle size of clinoptilolite on aflatoxin binding. Methods Fifteen commercial Greek dairy herds with AFM1 concentrations in bulk tank milk ≥0.05 μg/kg were selected. Bulk tank milk AFM1 was determined prior to the onset and on day 7 of the experiment. Clinoptilolite was added in the total mixed rations of all farms at the rate of 200 g per animal per day, throughout this period. Two different particle sizes of clinoptilolite were used; less than 0.15 mm in 9 farms (LC group) and less than 0.8 mm in 6 farms (HC group). Results Clinoptilolite administration significantly reduced AFM1 concentrations in milk in all farms tested at an average rate of 56.2 % (SD: 15.11). The mean milk AFM1 concentration recorded on Day 7 was significantly (P  < 0.001) lower compared to that of Day 0 (0.036 ± 0.0061 vs. 0.078 ± 0.0074 μg/kg). In LC group farms the reduction of milk AFM1 concentration was significantly higher than HC group farms (0.046 ± 0.0074 vs. 0.036 ± 0.0061 μg/kg, P  = 0.002). As indicated by the Pearson correlation, there was a significant and strong linear correlation among the milk AFM1 concentrations on Days 0 and 7 (R = 0.95, P  < 0.001). Conclusions Dietary administration of clinoptilolite, especially of smallest particle size, at the rate of 200 g per cow per day can effectively reduce milk AFM1 concentration in dairy cattle and can be used as a preventive measure for the amelioration of the risks associated with the presence of aflatoxins in the milk of dairy cows.